Too Much Television? Prospective Associations Between Early Childhood Televiewing and Later Self-reports of Victimization by Sixth Grade Classmates. Issue 6 (July 2015) - Watt, Emmalyne; Fitzpatrick, Caroline; Derevensky, Jeffrey L.; Pagani, Linda S.
ABSTRACT: Background: Using a birth cohort, this study aimed to verify whether televiewing at 29 months, a common early childhood pastime, is prospectively associated with self-reported victimization at age 12. Methods: Participants are 991 girls and 1006 boys from the Quebec Longitudinal Study of Child Development. The main predictor comprised parent-reported daily televiewing by their children at 29 months. In the sixth grade, children reported how often they experienced victimization by classmates in the past year. The authors conducted multivariate linear regression, in which child self-reports of victimization were linearly regressed on early televiewing and potential confounders. Results: Every SD unit increase (0.88 hours) in daily televiewing at 29 months predicted an 11% SD unit increase in self-reported peer victimization by sixth grade classmates (unstandardized B = .031, p < .001, 95% confidence interval = 0.014–0.042). This relationship was adjusted for child characteristics (gender, preexisting externalizing behaviors, baseline cognitive abilities, and televiewing at age 12) and family characteristics (family configuration, income, and functioning, and maternal education). Conclusions: Daily televiewing time at 29 months was associated with a subsequent increased risk of victimization by classmates at the end of sixth grade, a period which represents a critical developmental transition to middle school. Youth who experience peer victimization are at an increased risk of long-term mental health issues, such as depression, underachievement, and low self-esteem. This prospective association, across a 10-year period, suggests the need for better parental awareness, acknowledgement, and compliance with existing recommendations put forth by the American Academy of Pediatrics.